Implementation of the Nursing Services Management Model in 16 hospitals - Elizabeth Akemi Nishio; Letícia de Fatima Lazarini; Maria Elisabete Salvador; Maria D'Innocenzo (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to describe the main aspects and relevant results of the implementation of the Nursing Services Management Model in hospitals managed by social health organization, from 1998 to 2018. Methods: experience report of the model implemented in 16 hospitals in the state of São Paulo, Brazil. Results: the actions and monitoring of the implementation were based on protocols considering: management model and structure of the nursing service in hospitals; care process and main nursing care results; and people development. Final Considerations: the implementation of methods that ensure the well-being of nursing professionals is directly related to effective care, in which the practice is driven by quality and autonomy. Promoting a culture of care excellence, at different levels of management and care, has generated better expectations and motivation. It was found that the commitment of managers, by providing resources, resulted in improvements in the quality of nursing services.